Long-term (nearly a century) effects of fertilizer, lime and rice straw compost application on active aluminum and iron and available phosphorus in paddy fields - Ando, Kaori; Yamaguchi, Noriko; Kasuya, Masahiro; Oga, Toshiya; Ohashi, Yoshinori; Taki, Katsutoshi (Geoderma, 2022)
In paddy soils, plant availability of phosphorus (P) increases during the flooding period due to the reductive dissolution of iron (Fe)-bearing minerals on which P is sorbed. Soil chemical properties are a determining factor of P availability and are subject to change after prolonged paddy rice cultivation. The purpose of this study was to evaluate the effects of long-term application of rice straw compost and slaked lime on changes in soil chemical properties, particularly focusing on the increase in available P under reductive conditions. The rice cultivation experiment was launched in 1926 to clarify the effects of mineral fertilizer (NPK), rice straw compost, and slaked lime application on soil properties. The amount of P solubilized under reductive conditions was evaluated by the difference in the P extracted by the Bray II method with and without reductive treatment of the soil. Continuous application of NPK mineral fertilizer without slaked lime resulted in higher amounts of aluminum extracted by acid ammonium oxalate and P extracted by the Bray II method until the 92ⁿᵈ cropping, while the increase in the proportion of available P under reductive conditions was low. In contrast, the amounts of Fe extracted by acid ammonium oxalate and P solubilized under reductive conditions were higher with increasing application of compost. The application of the compost caused strongly reductive conditions in the soil during the flooding period, and the dissolution of P in the Fe-bound fraction was facilitated. However, excessive application of compost led to the dissolution of high amounts of Fe-bound P, resulting in a loss of Fe and P from the cultivated soil. These results suggest that excessive application of rice straw compost and no application of slaked lime may cause a decrease in available P in paddy soils.